Immunosenescence and immunecheckpoint inhibitors in non-small cell lung cancer patients: Does age really matter?. (November 2017) - Ferrara, Roberto; Mezquita, Laura; Auclin, Edouard; Chaput, Nathalie; Besse, Benjamin
Highlights: Immunosenescence is a progressive remodeling of immune functions with aging. In preclinical models, T-cells senescence is driven by targetable intracellular pathways. Ageing may correlate with accelerated tumor growth during immunotherapy. Efficacy data of ICIs in elderly NSCLC patients from phase III trials are conflicting. Retrospective, real-life studies showed superimposable survival in younger and older patients. Abstract: Immunotherapy has dramatically changed the therapeutic scenario in non-small cell lung cancer (NSCLC), extending overall survival, with a favorable safety profile. However, there is still a gap of knowledge about the efficacy of immune checkpoint inhibitors (ICIs) in elderly patients. Data from randomized clinical trials testing ICIs are conflicting and often lack adequate statistical power. Although two large meta-analyses suggested an absence of a significant survival benefit in patients older than 75 years, expanded access programs and retrospective cohort studies of ICIs in the real-life setting, showed comparable survival outcomes and safety profiles between older and younger patients. In this complex scenario, a further unresolved issue is the potential correlation between older age and immunotherapy primary resistance, a phenomenon probably linked to the continuous and progressive remodeling of immune functions with ageing, known as immunosenescence. Defining the role of ICIs in elderly NSCLC patients and exploring the molecular mechanisms underlying a possible lack of benefit or even accelerated tumor growth during immunotherapy are two major challenges for future research in this field of cancer treatment. In this review, we describe the major hallmarks of immunosenescence and we summarize the existing clinical data of ICIs in elderly NSCLC patients.